The Role ofOffice Spatial Planning in Improving Employee Performance BPS (Central Bureau of Statistics) Labuhan Batu Regency, North Sumatra - Melati Devyana; Muhammad Irwan Padli Nasution (Journal of Indonesian Management, 2022)
The purpose of the study was to find out how the role of Office Spatial Planning on Employee Performance at BPS (Central Bureau of Statistics) Labuhanbatu Regency. The method used in this research is descriptive research with a qualitative approach. Data was collected by means of interviews and documentation, and used primary and secondary data. The results of the study show that all the indicators that the authors mention above are very much needed to improve employee performance at BPS Labuhanbatu. Because, one of the things that become the standard to meet these demands is the layout of the office and all office facilities, if fulfilled, it will indirectly affect job satisfaction and work productivity. The more employee needs are met, the more satisfied the employee will be and this can improve employee performance at the Central Bureau of Statistics of Labuhan Batu Regency.